2016
DOI: 10.1002/cam4.840
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of in vivo antitumor effects of low‐frequency ultrasound‐mediated miRNA‐133a microbubble delivery in breast cancer

Abstract: MicroRNAs (miRNAs), as a novel class of small noncoding RNAs, have been identified as important transcriptional and posttranscriptional inhibitors of gene expression. Ultrasound‐targeted microbubble destruction (UTMD) is a noninvasive method for microRNA delivery. We aimed to investigate the effect of UTMD of miR‐133a on breast cancer treatment. It has been reported that miRNA‐133a is involved in various cancers. miR‐133a was lowly expressed in breast cancer tissues and breast cancer cell lines MCF‐7 and MDA‐M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 19 publications
0
44
0
Order By: Relevance
“…Numerous miRNAs reportedly function either as oncogenes or anti-oncogenes. Studies have indicated that miRNAs are often aberrantly regulated and play prohibitive or oncogenic roles in breast cancer (16,17). Recently, the clinical significance of miR-1254 has been verified, along with its role in tumorigenesis and progression, including lung cancer, thyroid cancer and oral squamous cell carcinoma (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous miRNAs reportedly function either as oncogenes or anti-oncogenes. Studies have indicated that miRNAs are often aberrantly regulated and play prohibitive or oncogenic roles in breast cancer (16,17). Recently, the clinical significance of miR-1254 has been verified, along with its role in tumorigenesis and progression, including lung cancer, thyroid cancer and oral squamous cell carcinoma (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…These methods are used in combination with other methods, such as lipofection, to protect nucleic acid against degradation by nucleases. To increase gene delivery efficiency of sonoporation, microbubbles were shown to be effective [43] and applied for delivery to cancer cells [44,45] and the central nervous system [46,47]. Clinical trials in phases I and II have been reported for the treatment of melanoma [48][49][50] and solid tumors [51].…”
Section: Sonoporation Electroporation and Magnetofectionmentioning
confidence: 99%
“…The therapeutic potential of miRNA-based agents has been investigated in in vivo models of many types of cancers [68][69][70][71][72][73][74] . Systemic delivery methods, such as encapsulation of miRNAs in nanoparticles or chemical modification of miRNAs, could be an effective technique for personalized therapies and cancer treatments [68] .…”
Section: Mirnas In Neuroblastoma Differentiation Therapymentioning
confidence: 99%